2014
DOI: 10.1055/s-0034-1381235
|View full text |Cite
|
Sign up to set email alerts
|

Sticky Platelet Syndrome: History and Future Perspectives

Abstract: The sticky platelet syndrome (SPS) is a thrombophilic qualitative platelet disorder with familial occurrence and autosomal dominant trait, characterized by increased in vitro platelet aggregation after low concentrations of adenosine diphosphate and/or epinephrine. Its clinical manifestation includes arterial thrombosis, pregnancy complications (fetal growth retardation and fetal loss), and less often venous thromboembolism. SPS was considered to be a rare thrombophilic disorder, but it can be found relatively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 51 publications
(68 reference statements)
1
18
0
Order By: Relevance
“…Other authors have also shown increased prevalence of obstetric complications in patients with SPS [ 18 , 19 , 31 ]. For example, our group demonstrated that, in the general Mexican population, the prevalence of SPS and the 677 mutation in the MTHFR gene is 15% and 79%, respectively [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other authors have also shown increased prevalence of obstetric complications in patients with SPS [ 18 , 19 , 31 ]. For example, our group demonstrated that, in the general Mexican population, the prevalence of SPS and the 677 mutation in the MTHFR gene is 15% and 79%, respectively [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, there is a shortage of literature on this syndrome in the pregnant population. Since the treatment of SPS is simple, cheap, and highly effective, employing aspirin and/or other antiplatelet drugs [ 13 , 16 ], the investigation of SPS in women treated for obstetric complications may be useful and deserves further research. The appropriate use of aspirin and/or other antiplatelet drugs during the pregnancy of patients with SPS could result in the prevention of adverse pregnancy outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is confirmed by predominance of platelets in such thrombin (so-called ‘white’ thrombi) and by efficiency of antiplatelet agents [ 15 ]. Altered platelet adhesion and aggregation due to increased vWF concentration, decreased ADAMTS13 (a metalloproteinase, that cleaves vWF to smaller, less procoagulant forms), increased in vitro platelet aggregation after low concentrations of adenosine diphosphate and/or epinephrine (sticky platelet syndrome) are associated with arterial thrombosis [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Patients with SPS present with arterial and/or venous thrombosis and fetal loss. 512 Although the first patient with SPS was reported in 1983, 13 many physicians remain unfamiliar with this platelet defect and do not consider SPS when screening for thrombophilic risk factors. The diagnosis and classification of SPS relies on platelet aggregometry tests employing appropriate dilutions of 2 platelet aggregation inducers: ADP and EPI.…”
Section: Introductionmentioning
confidence: 99%